STAGES OF CREATING A STRATEGIC MANAGEMENT PLAN OF THE COMPANY (Academia Science Repository, 2023)
This article focuses on such a complex issue as the formation of a company's strategic plan. The concepts of strategic planning, business planning and budgeting are considered. The necessity of communication between them is determined. A summary of these plans is given.